Childhood dental injuries: a resiliency model of adaptation. Issue 4 (21st October 2014) - Porritt, Jenny M.; Rodd, Helen D.; Baker, Sarah R.
<x xml:space="preserve">Abstract</x> Background There is a paucity of research examining how children and their families adapt to traumatic dental injuries. Aim This study examined how clinical and psychosocial factors influence adaptation to this oral stressor using a theoretical framework of resiliency and adaptation. Design Children with traumatised permanent teeth, who were attending a UK dental hospital, completed questionnaires at baseline and at a 6 month follow‐up. Child questionnaires assessed coping styles, social support, and quality of life outcomes. Parents were also asked to complete questionnaires, which assessed previous stressors/strains on the family, social support, healthcare satisfaction, and family impacts. Data related to the child's dental injury were collected from clinical notes. Structural equation modelling and regression analyses were employed to analyse data. Results One hundred and eight children and 113 parents participated at baseline. Children's gender, coping style, social support, and family functioning significantly predicted children's oral health‐related quality of life. Parents' satisfaction with their children's dental care significantly predicted parental quality of life outcomes. Children's close friend support and healthcare satisfaction remained significant predictors of positive outcomes at follow‐up. Conclusions The findings revealed important psychosocial factors that influence child and family adaptation to childhood dental trauma.